Re-thinking arts engagement in COVID-19: findings from a hybrid-delivered participatory arts intervention for Singapore's older adults - Yam, Jodie (Nanyang Technological University, 2022)
Healthy ageing has become an urgent public health concern that has stimulated the search for accessible, meaningful engagement for the ageing population. The participatory arts (PA) have since been hailed as an effective instrument for healthy ageing, having demonstrated overwhelming efficacy in promoting health outcomes. However, there is dearth of research on the cross-cultural expansion of PA interventions, and the ability of hybrid-delivered PA interventions to retain efficacy in an era of great social-distancing. Through a randomised controlled trial design, the present study answers these research gaps by examining the efficacy and underlying mechanisms of a culturally-adapted, hybridised translation of an existing PA intervention to Singapore.